Total Synthesis of Sporolide B and 9-epi-Sporolide B - Nicolaou, K. C. (2010)
The total synthesis of the structurally unique secondary metabolite sporolide B (1b, Figure 1) is described. The total synthesis of 1b was developed on the basis of preliminary studies that revealed the reactivity of an appropriate o-quinone as a diene system toward a number of indene derivatives as dienophiles, first in intermolecular and thence intramolecular settings. Thus, substrates were devised (37, Scheme 5; 75, Scheme 11) that underwent exquisite intramolecular [4+2] cycloaddition reactions under thermal conditions to provide primitive sporolide-type structures that were subsequently elaborated to sporolide model system 4 (Figure 1), 9-epi-sporolide B (5, Figure 1), and sporolide B (1b). The requisite indene o-quinone precursor (75, Scheme 10) was synthesized through a rutheniumcatalyzed [2+2+2] cycloaddition reaction between a propargylic alcohol (42, Figure 8) and a chloroacetylenic cyclopentenyne (64, Scheme 9) followed by elaboration and silver-promoted oxidation of the resulting chloroindene derivative. In addition to the total synthesis of 1b, this work demonstrated, for the first time, the power of the intramolecular hetero [4+2] cycloaddition reaction in the total synthesis of complex molecules and the application of the ruthenium-catalyzed [2+2+2] cycloaddition reaction to highly substituted indene systems possessing a chlorine residue on the aromatic nucleus.